2017
DOI: 10.18632/oncotarget.20567
|View full text |Cite
|
Sign up to set email alerts
|

Peri-treatment change of anorectal function in patients with rectal cancer after preoperative chemoradiotherapy

Abstract: Preoperative chemoradiotherapy (PCRT) is a standard treatment for locally advanced rectal cancer. The influence of PCRT on anorectal function has not been objectively assessed. We evaluated the short-term influence of PCRT on anorectal function in patients with locally advanced rectal cancer using anorectal manometry. We included 310 patients with locally advanced mid and lower rectal cancer who underwent PCRT from 2012 to 2015. We compared anorectal function based on anorectal manometry between before and aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…In this study, change in the MRST immediately after CRT showed a decrease in statistical significance. This finding is in accordance with that in previous studies on anorectal function post-CRT in patients with rectal cancer [11,[16][17][18]. To explain the reduced MRST post-CRT, Song et al [18] investigated the acute inflammation and edema caused by radiation exposure to the rectum.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In this study, change in the MRST immediately after CRT showed a decrease in statistical significance. This finding is in accordance with that in previous studies on anorectal function post-CRT in patients with rectal cancer [11,[16][17][18]. To explain the reduced MRST post-CRT, Song et al [18] investigated the acute inflammation and edema caused by radiation exposure to the rectum.…”
Section: Discussionsupporting
confidence: 89%
“…The manometric data from a small number of patients with midto low rectal cancer reported a significant reduction in anal resting and squeezing pressures measured immediately after CRT [11,17]. Contrarily, a recent study evaluating the change of anorectal function in patients with low rectal cancer demonstrated an increased anal resting pressure and slightly decreased squeezing pressure measured shortly after neoadjuvant CRT [16]. Such a variation can be explained partly by different techniques in anorectal manometry.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the sample size was relatively small and, in particular, there were few cases of CRT (2/68 patients, 3%). As such we have insufficient data to confirm or refute a possible negative effect of CRT on anorectal function after ISR . Third, the duration of follow‐up was short.…”
Section: Discussionmentioning
confidence: 97%
“…[24] Pharmacological analgesia, as the main modality for the treatment of colorectal cancer pain, has formed a 3-step analgesic treatment principle. [25][26][27][28] However, a large number of studies have found that the therapeutic effect of long-term analgesic drugs is not ideal, and the incidence of adverse reactions in patients after treatment is relatively high, which not only affects the clinical treatment but also has a great impact on the quality of life of patients. [29] The use of mind mapping in the health education of cancer patients to evaluate the level of pain, medication compliance, and patient satisfaction has enabled patients to control their pain and acquire knowledge about medication after the intervention.…”
Section: Discussionmentioning
confidence: 99%